The hatfield squat - Metzger, R.; Hatfield, D.; Dinyer-McNeely, T.; Dawes, J. (Strength and Conditioning Journal, 2025)
The Hatfield squat can be programmed into a lower-body exercise program to enhance a variety of muscular qualities. Furthermore, this squat variation may be useful for Olympic weightlifters because of the greater upright torso angle compared with the back squat because it may be more biomechanically similar to the starting position of a clean or snatch. From a rehabilitation standpoint, athletes with range of motion issues in the shoulders may benefit from this exercise because the hand positioning decreases the stress placed on this joint. Furthermore, athletes rehabilitating from lower extremity issues may also benefit from the balance and stability provided by holding the squat rack during this exercise movement.